Bridges, Stagecoaches, Trains and Balloons on the Road to the Tanzimat: Paintings and Descriptive Strategies of Modern Transportation Infrastructure and Vehicles in Seyyâhnâme ‘The Book of Traveller’ Dated 1835 - Fikret Turan (Art-Sanat)
The work entitled Seyyâhnâme presents a unique travel account as it provides detailed information about England and France and contains watercolour paintings on the subjects explained. The work was probably written by Mehmed Emin Pasha (d. 1851), a mühendishane military school-educated Ottoman statesman, between 1835-1837, at a time when he was studying at Cambridge University. There are two copies of the work, one of which is the author’s original copy (autograph) and the other is a later copy, and both copies are kept at the Library of Rare Works, Istanbul University. Theauthor enriched his work with 18 watercolour paintings to embody the subjects he expressed which include the modern military service, education, transportation infrastructure and modern vehicles that he witnessed in England. 14 of these paintings reflect modern transportation infrastructure such as streets, bridges and tunnels, as well as new-style passenger cars, steam trains and balloons, of which the author saw the originals or paintings in England. One of these images is a modern shopping street, showing London’s gas-powered street lamps, three of them show England’s prominent steel and suspension bridges, two of them tunnels pass under the river, one modern harbour and dock structure, two modern postal and passenger cars, two of them steam train and tram vehicles, and three of them balloons which had already started to be used for transportation purposes. It is understood that the author drew the pictures with new interpretations by using the pictures published in England as engravings or lithographs as templates. The author states that the subjects he describes are as seen in the pictures, and in this way, he implies that he is the painter of these pictures. This article examines how the author’s descriptions of transportation infrastructure and modern vehicles, which he describes with literary descriptions, are reflected in watercolour paintings.